Changes in aspects of children’s oral-health-related quality of life following dental treatment under general anaesthesia - H. K. ANDERSON, B. K. DRUMMOND & W. M. THOMSON (Paediatric Dentistry, 2004)
This study was intended to examine the treatment-associated change in aspects of oral-health-related quality of life (QoL) among children (and their families) undergoing dental rehabilitation under general anaesthesia (GA).